2017
DOI: 10.1038/ismej.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation enables free-living nitrogen-fixing rhizobacteria to fix nitrogen under aerobic conditions

Abstract: The multicellular communities of microorganisms known as biofilms are of high significance in agricultural setting, yet it is largely unknown about the biofilm formed by nitrogen-fixing bacteria. Here we report the biofilm formation by Pseudomonas stutzeri A1501, a free-living rhizospheric bacterium, capable of fixing nitrogen under microaerobic and nitrogen-limiting conditions. P. stutzeri A1501 tended to form biofilm in minimal media, especially under nitrogen depletion condition. Under such growth condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 57 publications
6
75
0
3
Order By: Relevance
“…In this study, we took advantage of the ability of A. brasilense to form biofilms and its consequent adherence to prepare a bioinoculant with organosolv-recovered lignin. We tracked the biofilm formation on lignin particles in different culture media [19,20]. We observed a good adhesion of bacterial particles to lignin as shown before; this could be explained in many ways, but we can attribute the facility of adherence to the fact that A. brasilense forms more stable biofilms in hydrophobic surfaces [20], which is the case of lignin.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In this study, we took advantage of the ability of A. brasilense to form biofilms and its consequent adherence to prepare a bioinoculant with organosolv-recovered lignin. We tracked the biofilm formation on lignin particles in different culture media [19,20]. We observed a good adhesion of bacterial particles to lignin as shown before; this could be explained in many ways, but we can attribute the facility of adherence to the fact that A. brasilense forms more stable biofilms in hydrophobic surfaces [20], which is the case of lignin.…”
Section: Discussionsupporting
confidence: 53%
“…We observed a good adhesion of bacterial particles to lignin as shown before; this could be explained in many ways, but we can attribute the facility of adherence to the fact that A. brasilense forms more stable biofilms in hydrophobic surfaces [20], which is the case of lignin. Also, it seems that lack of nitrogen negatively affected the biofilm formation after 3 days, after which they started to diminish in relative biomass; different from Pseudomonas stutzeri A1501, which forms more biofilms under nitrogen-depleted conditions [19].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Diazotrophs are either free-living or symbiotically associated with plants. Intensive studies have been conducted on symbiotic diazotrophs, while more and more studies have revealed the importance of free-living diazotrophs to N inputs in natural ecosystems (Reed et al, 2011;Reed et al, 2013;Wang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Оценка содержания нуклеиновых кислот в матриксе биопленок. Выделение компонентов матрикса и определение содержания в них нуклеиновых кислот проводили согласно рекомендациям, приведенным в работе [18]. Биомассу 6-суточных биопленок, сформированных на поверхности стекла, после удаления планктонных бактерий промывали 50 мМ ФБ (pH 7.0) и смывали пипетированием этим буфером.…”
Section: материалы и методыunclassified